THE CRISIS OF TRUST IN THE LEADERSHIP SYSTEM PORTRAYED IN INDONESIAN SHORT STORIES: A SOCIOLOGICAL LITERATURE STUDY - Wijianto, Agung; Pradnyan, Swastya Dharma (JURNAL LITERASI, 2024)
The Antologi Cerpen Indonesia-Malaysia is a collection of works by writers who share a common linguistic background: the Malay language. In addition to linguistic similarities, the social life of the communities also exhibits commonalities. This is reflected in the three short stories featured in the anthology: Bendera Yang Kembali Berkibar, Dialog Dua Generasi, dan Mencuri Perahu. This study aims to describe the reflection of the world of ideas and concepts in relation to the reality of societal life, considering that the writers share a historical background of having experienced colonization. A prominent discourse in each story is the crisis of trust, which is vividly portrayed in the characters' debates. The research method used is descriptive-analytical, with a sociological approach to literature. The analysis goes beyond merely explaining the narratives; it also seeks to provide an understanding that aligns with the study's focus. The findings of this research reveal the reality of the crisis of trust in leadership within society, the representation of this crisis in the three short stories, and the connection between the literary works and the social realities of the communities they reflect.